Color and hardness changes in artificial white spot lesions after resin infiltration - Ji-Hoon Kim (Restorative Dentistry & Endodontics, 2012)
Objectives The purpose of this study was to determine the effect of resin infiltration technique on color and surface hardness of white spot lesion (WSL) with various degrees of demineralization.